The role of anthropometry, physical, psychological and personality for elite athletes in competitive sports - Tri Setyo Guntoro; Sutoro; Miftah Fariz Prima Putra; Kurdi; Zsolt Németh; Edi Setiawan (IP Iermakov S.S., 2023)
Background and Study Aim. This study aims to describe and explore the anthropometric, physical, psychological, and personality traits of elite Papuan Indonesian athletes in seven different sports, namely weightlifting, rowing, cricket, futsal gateball, sailing, and hang-gliding. Material and Methods. A total of 118 athletes (80 men, 38 women with a mean age of 25.05±6.9) from these seven categories were selected. Furthermore, the anthropometric measurement consists of height, weight, and body mass index. At the same time, physical ability is made up of five components, namely flexibility, arm muscle strength, abdominal muscle strength, leg muscle power, and aerobic endurance. The psychological ability and personality characteristics were also measured using the Psychological Skill Inventory for Sport (PSIS) and the Athlete's Personality Inventory (IKA). Results. There were significant differences in the six variables (p<0.01), but no significant difference in the other variables (p>0.05). The six variables include height, BMI, arm and abdominal muscle strength, leg muscle power, and aerobic endurance with F and p-values of 3.052 and 0.008 (p<0.01), 3.497 and 0.003 (p<0.01), 9.822 and 0.001 (p<0.01), 11.855 and .001 (p <0.01), 52.747 and 0.001 (p<0.01), and 11.298 and 0.001 (p<0.01). The other four variables include weight, flexibility, psychological abilities, and personality traits, showed no significant difference (p>0.05). Aerobic endurance variables, in general, had a significant relationship with anthropometric variables and other physical aspects. However, psychological variables and personality characteristics did not significantly correlate with other variables. Conclusions. The anthropometric and physical aspects of athletes tended to have differences based on sports. However, psychological variables and personality characteristics had no relationship with physical and anthropometric aspects.